2014
DOI: 10.1016/j.juro.2014.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Statin Drug Use is Not Associated with Prostate Cancer Risk in Men Who are Regularly Screened

Abstract: Purpose Prospective cohort studies support that statin drug users have a lower risk of aggressive prostate cancer. Whether statin drug use influences risk of screen-detected disease is less clear, possibly because of complex detection biases. Thus, we investigated this association in a setting in which men had low baseline serum PSA concentration and were screened annually Methods We conducted a cohort study of 9,457 men aged ≥55 years old at randomization to the placebo arm of the Prostate Cancer Prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…Clinical reports have shown that statin use is beneficial for overall survival and cancer-specific survival both before and after prostate cancer diagnosis (1,2). In contrast, Platz et al reported that the use of statin drugs was not associated with the overall risk of prostate cancer (3). In vitro, statins exert many biological activities that inhibit prostate cancer progression (e.g., lowering raft cholesterol content, inhibiting cyclin-dependent-kinase-2 activity, decreasing IGF1 receptor expression, and increasing ANXA10 expression) (4,5,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical reports have shown that statin use is beneficial for overall survival and cancer-specific survival both before and after prostate cancer diagnosis (1,2). In contrast, Platz et al reported that the use of statin drugs was not associated with the overall risk of prostate cancer (3). In vitro, statins exert many biological activities that inhibit prostate cancer progression (e.g., lowering raft cholesterol content, inhibiting cyclin-dependent-kinase-2 activity, decreasing IGF1 receptor expression, and increasing ANXA10 expression) (4,5,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that statins can prolong survival, while others have reported no benefits in cancer patients (1). Concerning prostate cancer, the anticancer effect of statins is controversial (2,3). We previously reported that statins inhibit prostate cancer progression via suppressing the expression of insulin-like growth factor 1 receptor (IGF1R) and increasing ANXA10 (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Two observational studies which evaluated the placebo arm of two different randomized clinical trials (dutasteride/ finasteride for prostate cancer) and one observational study which evaluated the population from a prospective osteoporotic fracture in men study found no significant association between statin use and prostate cancer [23][24][25].…”
Section: Risk Of Prostate Cancer In Statin Usersmentioning
confidence: 99%
“…Randomized trials conducting PSA-independent biopsies at regular intervals may circumvent this potential source of detection bias, and secondary analysis of one such trial reported a null association between statin use and high-grade prostate cancer (24). However, given that trial participants are selected based upon specific eligibility criteria and do not represent a population-based sample, findings from secondary analyses of trials (21,24) may differ from findings reported by population-based studies (19,20), including our own. As such, although the potential for screening-related detection biases should be considered, our findings, in addition to those from populations with different PSA screening frequencies (25), support a true association between statin use and prostate cancer aggressiveness.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, analyses stratified by screening frequency showed a similar magnitude of inverse association between statin use and prostate cancer aggressiveness in men screened at high frequency (i.e., more than once a year), low, or recommended frequency (i.e., annually or less) and in unscreened men, suggesting that the association between statin use and prostate cancer aggressiveness cannot be completely explained by screening-related detection bias. In support of these findings, inverse associations between statin use and aggressive prostate cancer have been reported both in European populations with very low screening rates (19) and in U.S. populations with higher screening rates (20), although a secondary analysis of the Prostate Cancer Prevention Trial, wherein all participants were screened annually, reported no association between statin use and high-grade prostate cancer (21). Moreover, an analysis of simulated datasets with different PSA screening frequencies suggested that detection bias is unlikely to explain the association between statin use and reduced prostate cancer aggressiveness (18).…”
Section: Discussionmentioning
confidence: 87%